Availability bias and heterogeneity in saliency, recency, and frequency of promotions for plant-based foods: a naturalistic observation - McRae, Cameron; Dubé, Laurette (Frontiers in Behavioral Economics, 2024)
Availability bias influences decisions by how readily certain events, objects, or people can be brought to mind. This “out of sight, out of mind” effect depends on whether these elements are present during decision-making. To promote sustainable food consumption, understanding this bias is crucial, as marketing promotions exhibit heterogeneity in terms of the salience, recency, and frequency with which they are administered. Our research examines the impact of different promotions that vary across these three dimensions on the demand for plant-based food products and their interaction with price sensitivity. We analyzed weekly purchases of 21 plant-based beverage brands across 242 stores in Quebec, Canada, from 2015 to 2016 using two-level mixed-effect regression models across four studies. Results from Study 1 indicate that flyer promotions that had high salience, recency, and frequency were most effective (B = 0.417, p < 0.001), compared to mobile promotions with low salience and variable recency and frequency (B = 0.233, p < 0.001) or in-store promotions of high salience but low recency and frequency (B = 0.073, p < 0.001). Of the mobile promotions evaluated in Study 2, advertisements promoting bonus loyalty points were the most effective in driving demand (B = 0.776, p < 0.001), followed by general advertisements (B = 0.125, p < 0.001). Demand was elastic across all models, and most promotions increased price sensitivities in Studies 3 and 4 regardless of their salience, recency, or frequency. The findings highlight the synergistic effect of promotional elements delivered both before and at the decision-making moment in overcoming availability bias to boost demand for sustainable products. However, frequent promotions may increase price sensitivities due to anchoring to promotional prices. This article has implications for theory and practice.